Menghafal Al Qur`an Di Era Digital: Problematis Dan Metodologis. - Imam Sofii, Moh. Akib (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
Memorizing the Qur'an in the digital era presents complex challenges and requires appropriate methodologies. With the increasing dominance of information technology, Qur'an learners face various issues such as distractions from gadgets, declining interest in oral traditions, and psychological challenges due to lifestyle changes. However, there are approaches available to address these challenges, including utilizing technology as an aid, creating supportive environments, and strengthening motivation and self-discipline. By applying the right methodologies, Qur'an learners are expected to maintain the tradition of memorizing the Qur'an effectively and relevantly in this digital age.